Clinical and Radiological Outcomes of Open Vs Percutaneous Pedicle Screw Fixation for Traumatic Thoracolumbar Injuries - Khatri, Kuldip; Mehta, Bijay Kumar; Mahato, Mahendra P; Gurung, Praful; Wod, Rupesh (Purbanchal University Health Journal, 2025)
Introduction: Thoracolumbar fractures represent a challenging clinical scenario with potential for significant neurological deficits and impaired quality of life. Unstable thoracolumbar fractures need surgical stabilization to prevent further neurological deterioration as well as deformity. While open pedicle screw fixation has been the standard surgical procedure, percutaneous pedicle screw fixation is gaining popularity because of its less invasiveness. Objective: The study aims to compare the clinic-radiological outcomes of open pedicle screw fixation and percutaneous pedicle screw fixation in managing thoracolumbar fractures. Method: A prospective observational study was conducted at National Trauma Centre involving 42 patients with thoracolumbar vertebral fractures. Patients undergoing surgical management were divided in open pedicle screw fixation(OPSF) and percutaneous pedicle screw fixation(PPSF) group. Demographic data, injury details, clinical outcomes (VAS, ODI score)and radiographic measurements(AVBH, LKA) were recorded preoperatively and postoperatively at day 1,6 weeks and 6 months. Results were compared. Result: 42 patients were included, 21 in each group, of which29(69%) were male and 13(31%) were female with a mean age of 43 years. Significant postoperative clinical(VAS and ODI score) and radiological(AVBH and LKA) improvements were seen in both groups, as compared to the baseline. Statistically significant difference(p<0.05) in postoperative VAS and ODI scores was noted in percutaneous group as compared to open group. However, no significant difference(p>0.05) in radiological outcomes (AVBH, LKA) were observed between the two groups. Conclusion: Both the techniques showed similar radiological outcomes with no statistically significant differences in AVBH and LKA. However, PPSF exhibited superior clinical outcomes, with significantly lower ODI and VAS scores, indicating its potential as a favourable surgical approach for spinal stabilization.